2017
DOI: 10.1016/j.antiviral.2017.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of dapivirine, a nonnucleoside HIV-1 reverse transcriptase inhibitor, as a broad-spectrum antiviral against both influenza A and B viruses

Abstract: The emergence of multidrug-resistant influenza viruses poses a persistent threat to public health. The current prophylaxis and therapeutic interventions for influenza virus infection have limited efficacy due to the continuous antigenic drift and antigenic shift of influenza viruses. As part of our ongoing effort to develop the next generation of influenza antivirals with broad-spectrum antiviral activity and a high genetic barrier to drug resistance, in this study we report the discovery of dapivirine, an FDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 48 publications
0
31
0
Order By: Relevance
“…A time-of-addition experiment was performed according to the procedure described earlier 29 , 41 , 42 . Briefly, MDCK cells were seeded at 6 cm 2 dishes at a 2 × 10 5 cells/dish cell density.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A time-of-addition experiment was performed according to the procedure described earlier 29 , 41 , 42 . Briefly, MDCK cells were seeded at 6 cm 2 dishes at a 2 × 10 5 cells/dish cell density.…”
Section: Discussionmentioning
confidence: 99%
“…Serial drug passage experiments were performed accordingly to previously published protocol 29 , 30 , 42 . Briefly, MDCK cells were infected with the A/WSN/33 (H1N1) virus at MOI 0.001 for 1 h. Then the inoculum was removed and MDCK cells were incubated with 1 µM compound 12a in the first passage and the concentration of 12a was gradually increased 2-fold in passages 2–7 and kept constant at 64 µM in passages 7–10.…”
Section: Discussionmentioning
confidence: 99%
“…Similar membrane interacting molecules have been reported to interfere with virus-host membrane fusion mechanisms(13) and this may be a potential mechanism of action for this compound class.Dapivirine (IC50 = 0.73 µM) is a non-nucleoside reverse transcriptase inhibitor developed as an anti-HIV agent. It has been recently shown to have broad antiviral activity with in vitro micromolar IC50 values against influenza A and B(14). Almitrine (IC50 = 1.42 µM) was authorized for COPD later withdrawn after risk benefit balance reassessment(15).…”
mentioning
confidence: 99%
“…Therefore, new antiinfluenza drugs are being developed [52]. DR campaigns identified some drugs already approved or under clinical evaluation that showed anti-influenza properties, such as BAY 81-8781 (approved as intravenous Aspirin and exerting antiviral activity by blocking NF-kB pathway activation [53]), dapivirine (a non-nucleoside inhibitor of HIV-1 retrotranscriptase [54]), naproxen (which targets influenza nucleoprotein [55]), and the antibiotic clarithromycin. Clarithromycin and naproxen À along with oseltamivir in a three-drug combinationhave been evaluated in a phase 2b/3 clinical trial that showed efficacy in the treatment of severe influenza [56].…”
Section: Influenza Virusmentioning
confidence: 99%